Wall surface waterproof, crack-resistant and decorative integrated waterproof material and construction method thereof

By filling nanotitanium dioxide particles in the pores of sepiolite, forming a calcium stearate layer, and using bio-based polyurethane and olive leaf extract to form a cross-linking network structure, the problem of insufficient waterproofing and crack resistance of high-elastic acrylic waterproofing materials is solved, and higher mechanical strength and waterproofing properties are achieved.

CN119775840AInactive Publication Date: 2025-04-08NANJING SHUANGSHAN PAINT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964679.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The waterproofing performance of high-elastic acrylic waterproofing materials needs to be improved, and cracks are easy to be tested when external forces are applied. Adding sepiolite can improve mechanical properties, but its porous structure is easy to absorb water, resulting in a degradation of waterproofing performance. The skeleton of sepiolite is easily fragile after high temperature treatment.

Method used

The pores of sepiolite are filled with nanotitanium dioxide particles to form a calcium stearate layer, and a long-chain bio-based polyurethane is formed using glycerol monostearate and N-methyldiethanolamine to form a crosslinking network structure, combining olive leaf extracts.

Benefits of technology

It improves the mechanical strength and waterproof performance of sepiolite, enhances the crack resistance of waterproof materials, avoids the problem of sepiolite being easily absorbed, and improves the stability of the material after high temperature treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218055980000121
    Figure BDA0005218055980000121
  • Figure BDA0005218055980000131
    Figure BDA0005218055980000131
Patent Text Reader

Abstract

The invention discloses a wall surface waterproof crack-resistant decoration integrated waterproof material and a construction method thereof, and belongs to the technical field of building waterproof materials, the wall surface waterproof crack-resistant decoration integrated waterproof material comprises the following raw materials by mass: 100-120 parts of an acrylic acid waterproof emulsion, 10-12 parts of a reinforcing filler, 1.5-2 parts of an antifoaming agent, 1-2 parts of a thickening agent, 0.1-0.5 part of a preservative, 2-3 parts of an anti-freezing agent, and 70-90 parts of deionized water. In the reinforcing filler, a calcium stearate layer is formed on the surface of sepiolite loaded with nano-particles, so that excellent waterproof performance is achieved; a stearic acid chain of the modified sepiolite interacts with a hydrophobic chain in the olive leaf extract-bio-based polyurethane composite material to provide relatively high mechanical strength and waterproof performance, and when the waterproof material cracks, the olive leaf extract-bio-based polyurethane composite material in the reinforcing filler can be released to block the cracks, so that the waterproof performance is improved. The crack resistance of the waterproof material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building waterproof materials, and in particular to a wall waterproof crack-blocking decorative integrated waterproof material and a construction method thereof. Background Art

[0002] Waterproof materials are used to prevent the penetration of rainwater, snow water and groundwater, as well as to prevent the erosion of moisture, steam and other harmful gases and liquids in the air. They are mainly used in the roofs, walls, floors and basements of buildings to ensure the integrity and use functions of the structure. High-elastic waterproof coatings are high-performance waterproof coatings made of high-grade acrylic emulsion as the base material, with a variety of additives and fillers added and processed scientifically. Due to the addition of a variety of polymer additives, the waterproof performance of this product is better than that of ordinary waterproof products. At the same time, it has high-strength tensile ductility and can cover wall cracks.

[0003] High-elastic acrylic waterproof material blocks water penetration or water molecule infiltration by forming a complete waterproof coating, thus achieving waterproof effect. However, the waterproof performance of high-elastic acrylic waterproof material needs to be improved, and it is easy to crack when subjected to external force. Adding sepiolite to high-elastic acrylic waterproof material can improve the mechanical properties of the waterproof material, but the porous structure of sepiolite easily absorbs water, resulting in decreased waterproof performance, and the skeleton of sepiolite is fragile after high-temperature treatment. Summary of the invention

[0004] The purpose of the present invention is to provide an integrated waterproof material for wall waterproofing and crack prevention decoration and a construction method thereof: nano titanium dioxide particles are filled in the holes of sepiolite, on the one hand, the nano titanium dioxide particles serve as a supporting skeleton of the sepiolite to improve the mechanical strength of the sepiolite, and seal the pore structure of the sepiolite to prevent the sepiolite from absorbing water easily and causing the waterproof performance to decrease; a calcium stearate layer is formed on the surface of the sepiolite loaded with nano particles, and the formed calcium stearate layer has excellent waterproof performance, which further improves the waterproof performance of the sepiolite; monostearate glyceryl and N-methyldiethanolamine are used as polyols to react with the isocyanate group of toluene diisocyanate to form a long-chain bio-based polyurethane, and monostearate glyceryl provides a hydrophobic long-chain structure, so that the bio-based polyurethane has excellent waterproof performance; olive leaf extract and bio-based polyurethane form a cross-linked network structure with high mechanical strength, and when cracks appear in the waterproof material, the olive leaf extract-bio-based polyurethane composite material can be released to seal the cracks and improve the crack resistance of the waterproof material.

[0005] The technical problem to be solved by the present invention is as follows: the high-elastic acrylic waterproof material blocks the penetration of water or water molecules by forming a complete waterproof coating, thereby achieving a waterproof effect. However, the waterproof performance of the high-elastic acrylic waterproof material needs to be improved, and cracks are easily formed when an external force acts on it. Adding sepiolite to the high-elastic acrylic waterproof material can improve the mechanical properties of the waterproof material, but the porous structure of sepiolite easily absorbs water, resulting in a decrease in the waterproof performance, and the skeleton of sepiolite is easily broken after high-temperature treatment.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A wall waterproof crack-blocking decorative integrated waterproof material comprises the following raw materials in parts by mass: 100-120 parts of acrylic waterproof emulsion, 10-12 parts of reinforcing filler, 1.5-2 parts of defoaming agent, 1-2 parts of thickener, 0.1-0.5 parts of preservative, 2-3 parts of antifreeze agent and 70-90 parts of deionized water.

[0008] A method for preparing a wall waterproof crack-blocking decorative integrated waterproof material comprises the following steps:

[0009] The acrylic waterproof emulsion, reinforcing filler, defoamer, thickener, preservative, antifreeze agent and deionized water are mixed, stirred at 800-900 r / min for 20-30 min, heated to 70-80° C., and continued to stir for 1-2 h to obtain a waterproof material.

[0010] The acrylic waterproof emulsion is German BASF waterproof emulsion S400F.

[0011] Furthermore, the defoaming agent is selected from any one of emulsified silicone oil, fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether.

[0012] Furthermore, the thickener is selected from any one of methyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol.

[0013] Furthermore, the preservative is selected from 5-chloro-2-methyl-4-isothiazoline-3-one or 1,2-benzisothiazolin-3-one.

[0014] Furthermore, the antifreeze agent is selected from propylene glycol or glycerol.

[0015] Furthermore, the reinforcing filler is obtained by mixing and reacting olive leaf extract, modified sepiolite and bio-based polyurethane, and is specifically prepared by the following steps:

[0016] A1. Add olive leaf extract, fatty alcohol polyoxyethylene ether, and glacial acetic acid to deionized water, stir evenly, add bio-based polyurethane, and stir at 200r / min for 30min to obtain an olive leaf extract-bio-based polyurethane composite material;

[0017] A2. Mix the olive leaf extract-biobased polyurethane composite material, tristearin and modified sepiolite, stir at 200 r / min for 20 min, heat to 65°C, add glacial acetic acid and deionized water, stir and react at 300 rpm for 30 min, cool to room temperature, filter, and dry in an oven at 70°C for 10 min to obtain a reinforced filler.

[0018] Furthermore, during the reaction of step A1, N-methyldiethanolamine in the bio-based polyurethane is positively charged and can electrostatically adsorb to the hydroxyl and ester groups of the olive leaf extract, so that the olive leaf extract is evenly dispersed in the bio-based polyurethane to form an olive leaf extract-bio-based polyurethane composite material.

[0019] Furthermore, during the reaction process of step A2, the isocyanate in the olive leaf extract-bio-based polyurethane composite material can react with the hydroxyl group of tristearin, and the stearic acid chain of the modified sepiolite interacts with the hydrophobic chain in the olive leaf extract-bio-based polyurethane composite material, so that the modified sepiolite is embedded in the cross-linked network structure of the olive leaf extract-bio-based polyurethane composite material to form a reinforcing filler.

[0020] Furthermore, in step A1, the ratio of olive leaf extract, fatty alcohol polyoxyethylene ether, glacial acetic acid deionized water and bio-based polyurethane is (2-3) g: (0.5-0.7) g: (15-25) mL.

[0021] Furthermore, in step A2, the amount ratio of olive leaf extract-biobased polyurethane composite material, tristearate, modified sepiolite, glacial acetic acid and deionized water is (8-12) g: (7-9) g: (2-3) g: (0.3-0.7) g: (30-40) mL.

[0022] Furthermore, the bio-based polyurethane is specifically prepared by the following steps:

[0023] Glyceryl monostearate and toluene diisocyanate are mixed, heated to 60-70°C, stirred and reacted for 20-30 minutes, trimethylolpropane is added, stirred and reacted at 70-90°C for 20-30 minutes, cooled to 45-55°C, N-methyldiethanolamine is added, stirred and reacted for 25-35 minutes, cooled to room temperature, and bio-based polyurethane is obtained.

[0024] Furthermore, glyceryl monostearate and N-methyldiethanolamine, as polyols, react with the isocyanate of toluene diisocyanate to form a long-chain bio-based polyurethane. Glyceryl monostearate provides a hydrophobic long-chain structure, which makes the bio-based polyurethane have excellent waterproof properties.

[0025] Furthermore, the mass ratio of glyceryl monostearate, toluene diisocyanate, trimethylolpropane and N-methyldiethanolamine is (8-9):(4-5):(0.1-0.3):(0.2-0.4).

[0026] Furthermore, the olive leaf extract is specifically prepared by the following steps:

[0027] The olive leaves are washed with hydrochloric acid and dried, then added to ethanol, stirred at 40-50°C for 35-40 minutes, heated to 65-75°C, and stirred for 10-15 minutes to obtain a concentrate, which is filtered and dried at 70°C for 8 minutes to obtain an olive leaf extract.

[0028] Furthermore, the mass ratio of dried olive leaves to ethanol is (8-12) g:(65-75) mL.

[0029] Furthermore, the modified sepiolite is prepared by mixing and reacting the sepiolite loaded with nanoparticles with calcium chloride and stearic acid, and is specifically prepared by the following steps:

[0030] Calcium chloride was added to deionized water and stirred until completely dissolved. Nanoparticle-loaded sepiolite was added and stirred in a 30°C water bath for 10 minutes. Stearic acid was added and the reaction was continued with stirring for 25 minutes. The mixture was dried in an oven at 105°C overnight to obtain modified sepiolite.

[0031] Furthermore, the hydroxyl groups on the surface of the nanoparticle-loaded sepiolite can combine with the calcium ions in the calcium chloride, so that the calcium ions are deposited on the surface of the nanoparticle-loaded sepiolite, and the calcium ions can react with the carboxyl groups of stearic acid to form calcium stearate, thereby forming a calcium stearate layer on the surface of the nanoparticle-loaded sepiolite to obtain modified sepiolite.

[0032] Furthermore, the dosage ratio of calcium chloride, deionized water, nanoparticle-loaded sepiolite and stearic acid is (8-12) g:(80-120) mL:(4-6) g:(1-2) g.

[0033] Furthermore, the nanoparticle-loaded sepiolite is prepared by mixing sepiolite with tetrabutyl titanate and subjecting the mixture to a hydrothermal reaction, specifically by the following steps:

[0034] Sepiolite and tetrabutyl titanate were added to deionized water, stirred at 80°C for 30 min, placed in a polytetrafluoroethylene autoclave, hydrothermally treated at 150°C for 3 h, filtered, washed with deionized water three times, dried in an oven at 60°C for 10 min, calcined at 200°C for 2 h, and cooled to room temperature to obtain sepiolite loaded with nanoparticles.

[0035] Furthermore, the porous structure of sepiolite can adsorb tetrabutyl titanate into the porous structure of sepiolite. After a hydrothermal reaction at 150°C, tetrabutyl titanate is hydrolyzed to form titanium dioxide colloid, and then titanium dioxide colloid is synthesized in the pores of sepiolite. Further, after calcination at 200°C, the titanium dioxide colloid forms nano-titanium dioxide particles, thereby filling the pores of sepiolite with nano-titanium dioxide particles.

[0036] Furthermore, the usage ratio of sepiolite, tetrabutyl titanate and deionized water is (1-3) g:(8-12) mL:(20-30) mL.

[0037] Furthermore, the hydrothermal reaction temperature is 140-160° C., and the hydrothermal reaction time is 2-4 h.

[0038] Furthermore, the sepiolite has a particle size of 5-8 micrometers and a pore size of 100-200 nm.

[0039] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) In the technical solution of the present invention, nano-titanium dioxide particles are filled in the pores of sepiolite. On the one hand, the nano-titanium dioxide particles serve as a supporting skeleton of sepiolite to improve the mechanical strength of sepiolite and prevent the sepiolite skeleton from being fragile after high-temperature treatment, which may cause a decrease in the mechanical properties and crack resistance of the waterproof material. On the other hand, the pore structure of sepiolite is blocked to prevent sepiolite from easily absorbing water and causing a decrease in waterproof performance. As a fibrous hydrous magnesium silicate mineral, sepiolite can effectively increase the toughness of wall waterproof materials, and its fibrous structure can be interspersed into the wall waterproof material to improve the crack resistance of the wall waterproof material.

[0041] (2) In the technical solution of the present invention, a calcium stearate layer is formed on the surface of the nanoparticle-loaded sepiolite. The formed calcium stearate layer has excellent waterproof performance, which further improves the waterproof performance of the sepiolite and enhances the waterproof performance of the wall waterproof material. The fatty chains contained in the calcium stearate layer can be stably dispersed in the acrylic waterproof emulsion, thereby improving the compatibility between the modified sepiolite and the organic compound, and improving the mechanical properties, crack resistance and waterproof performance of the waterproof material.

[0042] (3) In the technical scheme of the present invention, glyceryl monostearate and N-methyldiethanolamine are used as polyols to react with the isocyanate group of toluene diisocyanate to form a long-chain bio-based polyurethane. Glyceryl monostearate provides a hydrophobic long-chain structure, which makes the bio-based polyurethane have excellent waterproof properties. The bio-based polyurethane can be electrostatically adsorbed with the olive leaf extract, so that the olive leaf extract is evenly dispersed in the polyurethane. The olive leaf extract contains a large number of hydroxyl and ester structures, which can be combined with the waterproof material through strong hydrogen bonds, thereby improving the bonding strength between the bio-based polyurethane and the waterproof material and enhancing the waterproof performance.

[0043] (4) In the technical scheme of the present invention, the isocyanate in the olive leaf extract-biobased polyurethane composite material can react with the hydroxyl group of tristearin to form a cross-linked network structure with high mechanical strength, and the stearic acid chain of the modified sepiolite interacts with the hydrophobic chain in the olive leaf extract-biobased polyurethane composite material, so that the modified sepiolite is embedded in the cross-linked network structure of the olive leaf extract-biobased polyurethane composite material, providing high mechanical strength and waterproof performance, and when cracks appear in the waterproof material, the olive leaf extract-biobased polyurethane composite material can be released to seal the cracks and improve the crack resistance of the waterproof material. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The raw materials used in the embodiments of the present invention are as follows:

[0046] Tetrabutyl titanate (purity 99%, Nantong Runfeng Petrochemical Co., Ltd.); calcium chloride (purity 74%, Weifang Ruidesheng Chemical Co., Ltd.); stearic acid (purity 99%, Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.); monostearic acid glyceryl (purity 99%, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.); toluene diisocyanate (purity 99%, Jiangsu Runfeng Synthetic Technology Co., Ltd.); trimethylolpropane (Hubei Jiahui Xingcheng Biotechnology Co., Ltd., purity 99%); N-methyldiethanolamine (Kunshan Sheng'an Biotechnology Co., Ltd., purity 99%); fatty alcohol polyoxyethylene ether (Shanghai Yuanye Biotechnology Co., Ltd., reagent grade); tristearic acid glyceryl (purity 99%, Shandong Polychemical Co., Ltd.).

[0047] The acrylic waterproof emulsion is German BASF waterproof emulsion S400F.

[0048] The particle size of sepiolite is 6 microns and the pore size is 150nm.

[0049] Olive leaf extract is specifically prepared by the following steps:

[0050] The olive leaves were washed with hydrochloric acid and dried at 60°C. 10 g of the dried olive leaves were added to 70 mL of ethanol and stirred at 45°C for 38 min. The mixture was heated to 70°C and stirred for 13 min to obtain a concentrated solution. The concentrated solution was filtered and dried at 70°C for 8 min to obtain an olive leaf extract.

[0051] Embodiment 1 The reinforcing filler is specifically prepared by the following steps:

[0052] A1. 2 g of sepiolite and 10 mL of tetrabutyl titanate were added to 25 mL of deionized water, stirred at 80 ° C for 30 min, placed in a polytetrafluoroethylene autoclave, hydrothermally treated at 150 ° C for 3 h, filtered, washed with deionized water 3 times, dried in an oven at 60 ° C for 10 min, calcined at 200 ° C for 2 h, and cooled to room temperature to obtain a sepiolite loaded with nanoparticles;

[0053] A2. Add 10 g of calcium chloride to 100 mL of deionized water, stir until completely dissolved, add 5 g of nanoparticle-loaded sepiolite, stir in a 30 ° C water bath for 10 min, add 1.5 g of stearic acid, continue stirring and reacting for 25 min, and dry in an oven at 105 ° C overnight to obtain modified sepiolite;

[0054] A3. 8.5 g of glyceryl monostearate and 4.5 g of toluene diisocyanate were mixed, heated to 65 ° C, stirred for 25 min, 0.2 g of trimethylolpropane was added, stirred for 25 min at 80 ° C, cooled to 50 ° C, 0.3 g of N-methyldiethanolamine was added, and the reaction was continued with stirring for 30 min, and cooled to room temperature to obtain a bio-based polyurethane;

[0055] A4. 2.5 g of olive leaf extract, 0.6 g of fatty alcohol polyoxyethylene ether, and 0.4 g of glacial acetic acid were added to 30 mL of deionized water, stirred evenly, 20 g of bio-based polyurethane was added, and stirred at 200 r / min for 30 min to obtain an olive leaf extract-bio-based polyurethane composite material;

[0056] A5. Mix 10g of olive leaf extract-biobased polyurethane composite material, 8g of tristearin and 2.5g of modified sepiolite, stir at 200r / min for 20min, heat to 65°C, add 0.5g of glacial acetic acid and 35mL of deionized water, stir and react at 300rpm for 30min, cool to room temperature, filter, and dry in an oven at 70°C for 10min to obtain a reinforced filler.

[0057] Comparative Example 1 The difference between this comparative example and Example 1 is that the sepiolite loaded with nanoparticles is replaced by sepiolite, and the remaining steps and raw materials are synchronized with Example 1.

[0058] A1. Add 10 g of calcium chloride to 100 mL of deionized water, stir until completely dissolved, add 5 g of nanoparticle-loaded sepiolite, stir in a 30 ° C water bath for 10 min, add 1.5 g of stearic acid, continue stirring and reacting for 25 min, and dry in an oven at 105 ° C overnight to obtain modified sepiolite;

[0059] A2. 8.5 g of glyceryl monostearate and 4.5 g of toluene diisocyanate were mixed, heated to 65 ° C, stirred for 25 min, 0.2 g of trimethylolpropane was added, stirred for 25 min at 80 ° C, cooled to 50 ° C, 0.3 g of N-methyldiethanolamine was added, and the reaction was continued with stirring for 30 min, and cooled to room temperature to obtain a bio-based polyurethane;

[0060] A3. 2.5 g of olive leaf extract, 0.6 g of fatty alcohol polyoxyethylene ether, and 0.4 g of glacial acetic acid were added to 30 mL of deionized water, stirred evenly, 20 g of bio-based polyurethane was added, and stirred at 200 r / min for 30 min to obtain an olive leaf extract-bio-based polyurethane composite material;

[0061] A4. Mix 10g of olive leaf extract-biobased polyurethane composite material, 8g of tristearin and 2.5g of modified sepiolite, stir at 200r / min for 20min, heat to 65°C, add 0.5g of glacial acetic acid and 35mL of deionized water, stir and react at 300rpm for 30min, cool to room temperature, filter, and dry in an oven at 70°C for 10min to obtain a reinforced filler.

[0062] Comparative Example 2 The difference between this comparative example and Example 1 is that the modified sepiolite is replaced by sepiolite loaded with nanoparticles, and the remaining steps and raw materials are the same as Example 1.

[0063] A1. 2 g of sepiolite and 10 mL of tetrabutyl titanate were added to 25 mL of deionized water, stirred at 80 ° C for 30 min, placed in a polytetrafluoroethylene autoclave, hydrothermally treated at 150 ° C for 3 h, filtered, washed with deionized water 3 times, dried in an oven at 60 ° C for 10 min, calcined at 200 ° C for 2 h, and cooled to room temperature to obtain a sepiolite loaded with nanoparticles;

[0064] A2. 8.5 g of glyceryl monostearate and 4.5 g of toluene diisocyanate were mixed, heated to 65 ° C, stirred for 25 min, 0.2 g of trimethylolpropane was added, stirred for 25 min at 80 ° C, cooled to 50 ° C, 0.3 g of N-methyldiethanolamine was added, and the reaction was continued with stirring for 30 min, and cooled to room temperature to obtain a bio-based polyurethane;

[0065] A3. 2.5 g of olive leaf extract, 0.6 g of fatty alcohol polyoxyethylene ether, and 0.4 g of glacial acetic acid were added to 30 mL of deionized water, stirred evenly, 20 g of bio-based polyurethane was added, and stirred at 200 r / min for 30 min to obtain an olive leaf extract-bio-based polyurethane composite material;

[0066] A4. Mix 10g of olive leaf extract-biobased polyurethane composite material, 8g of tristearin and 2.5g of sepiolite loaded with nanoparticles, stir at 200r / min for 20min, heat to 65°C, add 0.5g of glacial acetic acid and 35mL of deionized water, stir and react at 300rpm for 30min, cool to room temperature, filter, and dry in an oven at 70°C for 10min to obtain a reinforced filler.

[0067] Comparative Example 3 The difference between this comparative example and Example 1 is that no olive leaf extract is added, and the remaining steps and raw materials are the same as Example 1.

[0068] A1. 2 g of sepiolite and 10 mL of tetrabutyl titanate were added to 25 mL of deionized water, stirred at 80 ° C for 30 min, placed in a polytetrafluoroethylene autoclave, hydrothermally treated at 150 ° C for 3 h, filtered, washed with deionized water 3 times, dried in an oven at 60 ° C for 10 min, calcined at 200 ° C for 2 h, and cooled to room temperature to obtain a sepiolite loaded with nanoparticles;

[0069] A2. Add 10 g of calcium chloride to 100 mL of deionized water, stir until completely dissolved, add 5 g of nanoparticle-loaded sepiolite, stir in a 30 ° C water bath for 10 min, add 1.5 g of stearic acid, continue stirring and reacting for 25 min, and dry in an oven at 105 ° C overnight to obtain modified sepiolite;

[0070] A3. 8.5 g of glyceryl monostearate and 4.5 g of toluene diisocyanate were mixed, heated to 65 ° C, stirred for 25 min, 0.2 g of trimethylolpropane was added, stirred for 25 min at 80 ° C, cooled to 50 ° C, 0.3 g of N-methyldiethanolamine was added, and the reaction was continued with stirring for 30 min, and cooled to room temperature to obtain a bio-based polyurethane;

[0071] A4. Mix 10g of bio-based polyurethane, 8g of tristearin and 2.5g of modified sepiolite, stir at 200r / min for 20min, heat to 65°C, add 0.5g of glacial acetic acid and 35mL of deionized water, stir at 300rpm for 30min, cool to room temperature, filter, and dry in an oven at 70°C for 10min to obtain a reinforcing filler.

[0072] Comparative Example 4 The difference between this comparative example and Example 1 is that no bio-based polyurethane is added, and the remaining steps and raw materials are the same as Example 1.

[0073] A1. 2 g of sepiolite and 10 mL of tetrabutyl titanate were added to 25 mL of deionized water, stirred at 80 ° C for 30 min, placed in a polytetrafluoroethylene autoclave, hydrothermally treated at 150 ° C for 3 h, filtered, washed with deionized water 3 times, dried in an oven at 60 ° C for 10 min, calcined at 200 ° C for 2 h, and cooled to room temperature to obtain a sepiolite loaded with nanoparticles;

[0074] A2. Add 10 g of calcium chloride to 100 mL of deionized water, stir until completely dissolved, add 5 g of nanoparticle-loaded sepiolite, stir in a 30 ° C water bath for 10 min, add 1.5 g of stearic acid, continue stirring and reacting for 25 min, and dry in an oven at 105 ° C overnight to obtain modified sepiolite;

[0075] A3. 10 g of olive leaf extract and 2.5 g of modified sepiolite were mixed and stirred at 200 r / min for 20 min to obtain a reinforced filler.

[0076] Example 2 A wall waterproof and crack-blocking decorative integrated waterproof material comprises the following raw materials in parts by mass: 100-120 parts of acrylic waterproof emulsion, 10-12 parts of reinforcing filler prepared in Example 1, 1.5-2 parts of emulsified silicone oil, 1-2 parts of methyl cellulose, 0.1-0.5 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 2-3 parts of propylene glycol, and 70-90 parts of deionized water.

[0077] A method for preparing a wall waterproof crack-blocking decorative integrated waterproof material comprises the following steps:

[0078] Mix the acrylic waterproof emulsion, the reinforcing filler prepared in Example 1, emulsified silicone oil, methyl cellulose, 5-chloro-2-methyl-4-isothiazoline-3-one, propylene glycol and deionized water, stir at 800-900 r / min for 20-30 min, heat to 70-80° C., and continue stirring for 1-2 h to obtain a waterproof material.

[0079] Example 3 A wall waterproof and crack-blocking decorative integrated waterproof material comprises the following raw materials in parts by mass: 100-120 parts of acrylic waterproof emulsion, 10-12 parts of reinforcing filler prepared in Example 1, 1.5-2 parts of fatty alcohol polyoxyethylene ether, 1-2 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of 1,2-benzisothiazolin-3-one, 2-3 parts of glycerol, and 70-90 parts of deionized water.

[0080] A method for preparing a wall waterproof crack-blocking decorative integrated waterproof material comprises the following steps:

[0081] Mix the acrylic waterproof emulsion, the reinforcing filler prepared in Example 1, fatty alcohol polyoxyethylene ether, hydroxypropyl methylcellulose, 1,2-benzisothiazolin-3-one, glycerol and deionized water, stir at 800-900 r / min for 20-30 min, heat to 70-80° C., and continue stirring for 1-2 h to obtain a waterproof material.

[0082] Example 4 A wall waterproof and crack-blocking decorative integrated waterproof material comprises the following raw materials in parts by mass: 100-120 parts of acrylic waterproof emulsion, 10-12 parts of reinforcing filler prepared in Example 1, 1.5-2 parts of alkylphenol polyoxyethylene ether, 1-2 parts of polyvinyl alcohol, 0.1-0.5 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 2-3 parts of propylene glycol, and 70-90 parts of deionized water.

[0083] A method for preparing a wall waterproof crack-blocking decorative integrated waterproof material comprises the following steps:

[0084] Mix the acrylic waterproof emulsion, the reinforcing filler prepared in Example 1, alkylphenol polyoxyethylene ether, polyvinyl alcohol, 5-chloro-2-methyl-4-isothiazoline-3-one, glycerol and deionized water, stir at 800-900 r / min for 20-30 min, heat to 70-80° C., and continue stirring for 1-2 h to obtain a waterproof material.

[0085] Comparative Example 5 The difference between this comparative example and Example 3 is that the reinforcing filler prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 3.

[0086] Comparative Example 6 The difference between this comparative example and Example 3 is that the reinforcing filler prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 3.

[0087] Comparative Example 7 The difference between this comparative example and Example 4 is that the reinforcing filler prepared in Example 1 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 3.

[0088] Comparative Example 8 The difference between this comparative example and Example 3 is that the reinforcing filler prepared in Example 1 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 3.

[0089] The performance of the waterproof materials prepared in Examples 2-4 and Comparative Examples 5-8 is now tested;

[0090] The construction method of the waterproof material is specifically as follows: the prepared waterproof material is applied to the wall surface, and then the spunbonded non-woven fabric is attached, and the waterproof material is applied after rolling and flattening with a roller to obtain a waterproof coating with a thickness of 2.5 mm. The waterproof coating is placed at 70° C. for 2 hours, and the surface of the waterproof coating is observed to see if there is any cracking.

[0091] Test the crack resistance of waterproof coating according to GB / T1732-1993 standard;

[0092] The waterproof material prepared above was tested according to the test methods of GB / T16777-2008 "Test Methods for Building Waterproof Coatings" and GB / T9756-2009 "Synthetic Resin Emulsion Interior Wall Coatings";

[0093] The test results are shown in Table 1 below:

[0094] Table 1

[0095]

[0096]

[0097] It can be seen from the data in Table 1 that in Comparative Example 5, the sepiolite loaded with nanoparticles is replaced with a reinforcing filler prepared from sepiolite and added to the waterproof material, and its waterproof performance and mechanical properties are reduced. This may be because nano-titanium dioxide particles are filled in the pores of sepiolite. On the one hand, the nano-titanium dioxide particles serve as a supporting skeleton of sepiolite, which improves the mechanical strength of sepiolite and avoids the mechanical properties and crack resistance of the waterproof material being reduced due to the fragility of the skeleton after high-temperature treatment of sepiolite. However, the surface of sepiolite lacks nanoparticles and cannot achieve this effect, so the waterproof performance and mechanical properties are reduced.

[0098] In Comparative Example 6, the modified sepiolite is replaced with a reinforcing filler prepared from sepiolite loaded with nanoparticles, and added to the waterproof material. The waterproof performance and mechanical properties thereof are reduced. This may be because a calcium stearate layer is formed on the surface of the sepiolite loaded with nanoparticles, which enhances the mechanical properties, crack resistance and waterproof performance of the wall waterproof material. However, the surface of the sepiolite loaded with nanoparticles lacks a calcium stearate layer, and this effect cannot be achieved. Therefore, the mechanical properties and flame retardant properties are reduced.

[0099] Comparative Example 7: When the reinforcing filler prepared without olive leaf extract was added to the waterproof material, its waterproof performance and mechanical properties decreased. This may be because the olive leaf extract is evenly dispersed in the polyurethane. The olive leaf extract contains a large number of hydroxyl and ester structures, which can be combined with the waterproof material through strong hydrogen bonds, thereby improving the bonding strength between the bio-based polyurethane and the waterproof material and enhancing the waterproof performance. However, the reinforcing filler lacks olive leaf extract and cannot achieve this effect, so the wear resistance and mechanical properties decrease.

[0100] Comparative Example 8 is a reinforcing filler prepared without adding bio-based polyurethane. When it is added to the waterproof material, its waterproof performance and mechanical properties are reduced. This may be because the olive leaf extract-bio-based polyurethane forms a cross-linked network structure with high mechanical strength, and when cracks appear in the waterproof material, it can release the olive leaf extract-bio-based polyurethane composite material to seal the cracks and improve the crack resistance of the waterproof material. However, the lack of bio-based polyurethane in the reinforcing filler cannot achieve this effect, so the wear resistance and mechanical properties are reduced.

[0101] The data in Table 1 show that the waterproof materials prepared in Examples 2-4 meet the test performance requirements, while the waterproof materials prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the waterproof materials prepared in the present invention have good mechanical properties, crack resistance and waterproof properties.

[0102] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0103] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A wall waterproof crack-blocking decorative integrated waterproof material, characterized in that: The invention comprises the following raw materials in parts by weight: 100-120 parts of acrylic waterproof emulsion, 10-12 parts of reinforcing filler, 1.5-2 parts of defoaming agent, 1-2 parts of thickener, 0.1-0.5 parts of preservative, 2-3 parts of antifreeze agent and 70-90 parts of deionized water; The reinforcing filler is obtained by mixing and reacting olive leaf extract, modified sepiolite and bio-based polyurethane; The modified sepiolite is prepared by mixing and reacting sepiolite loaded with nanoparticles with calcium chloride and stearic acid; The nano-particle-loaded sepiolite is prepared by mixing sepiolite with tetrabutyl titanate and subjecting the mixture to a hydrothermal reaction.

2. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The sepiolite has a particle size of 5-8 microns and a pore size of 100-200 nm.

3. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The hydrothermal reaction temperature is 140-160° C., and the hydrothermal reaction time is 2-4 hours.

4. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The bio-based polyurethane is specifically prepared by the following steps: Glyceryl monostearate and toluene diisocyanate are mixed, heated to 60-70°C, stirred and reacted for 20-30 minutes, trimethylolpropane is added, stirred and reacted at 70-90°C for 20-30 minutes, cooled to 45-55°C, N-methyldiethanolamine is added, stirred and reacted for 25-35 minutes, cooled to room temperature, and bio-based polyurethane is obtained.

5. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 4, characterized in that: The mass ratio of glyceryl monostearate, toluene diisocyanate, trimethylolpropane and N-methyldiethanolamine is (8-9):(4-5):(0.1-0.3):(0.2-0.4).

6. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The olive leaf extract is specifically prepared by the following steps: The olive leaves are washed with hydrochloric acid and dried, then added to ethanol, stirred at 40-50°C for 35-40 minutes, heated to 65-75°C, and stirred for 10-15 minutes to obtain a concentrate, which is filtered and dried at 70°C for 8 minutes to obtain an olive leaf extract.

7. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The defoaming agent is selected from any one of emulsified silicone oil, fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether; the thickener is selected from any one of methyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol.

8. The wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The preservative is an isothiazolinone preservative; the antifreeze agent is selected from propylene glycol or glycerol.

9. The method for preparing a wall waterproof crack-blocking decorative integrated waterproof material according to claim 1, characterized in that: The steps include: The acrylic waterproof emulsion, reinforcing filler, defoamer, thickener, preservative, antifreeze agent and deionized water are mixed, stirred at 800-900 r / min for 20-30 min, heated to 70-80° C., and continued to stir for 1-2 h to obtain a waterproof material.

10. A construction method for a waterproof material prepared according to any one of claims 1 to 9, characterized in that: The specific construction method is: brushing the waterproof material on the wall surface, then laminating the spunbond non-woven fabric, rolling and flattening it with a roller, and then brushing the waterproof material to obtain a waterproof coating with a thickness of 2-3mm.